Selection on stability across ecological scales. (July 2015) - Borrelli, Jonathan J.; Allesina, Stefano; Amarasekare, Priyanga; Arditi, Roger; Chase, Ivan; Damuth, John; Holt, Robert D.; Logofet, Dmitrii O.; Novak, Mark; Rohr, Rudolf P.; Rossberg, Axel G.; Spencer, Matthew; et al.
Highlights Stability selection is a process generating similarity in ecological systems. Community configurations that are more stable should be observed more frequently. Selection resulting from the stability properties of the system is 'nonadaptive'. We can find examples of nonadaptive stability selection across ecological scales.